Madrid on the move : feeling modern and visually aware in the nineteenth century - Rodríguez-Galindo, Vanesa (Manchester University Press, 2021)
Madrid on the move offers an account of illustrated print culture and the urban experience in nineteenth-century Spain. It provides a fresh account of modernity from a transnational perspective. Drawing on different kinds of printed images and texts, the book explores what being modern meant to people in their daily lives.
Keywords: Madrid (Spain) -- Civilization -- 19th century.; Madrid (Spain) -- Social life and customs -- 19th century.; Civilization, Modern -- 19th century.; Illustrated periodicals -- Spain -- Madrid -- History -- 19th century.; Civilisation -- 19e siècle.; Magazines (Publications) -- Espagne -- Madrid -- Histoire -- 19e siècle.; Civilization; Civilization, Modern; Illustrated periodicals; Manners and customs; Spain -- Madrid; 1800-1899; Electronic books.; History